From Fences to Medicine: A Short Review on Ethnobotanical Study of Lannea coromandelica (Houtt.) Merr. (Family Anacardiaceae) in Indonesia - Raihandhany, Reza (Generasi Biologi Indonesia, 2022)
Lannea coromandelica (Houtt.) Merr. is a deciduous tropical tree that originates and is native to India. This species belongs to the family Anacardiaceae. L. coromandelica is also found in Indonesia and is known as kayu jawa. Indonesian people often utilize L. coromandelica for medicinal purposes and as natural fences. Almost all parts of the plant, including the bark, leaves, sap, and trunk, can be utilized for medicinal purposes. This paper review aims to gather information regarding ethnobotanical studies conducted by traditional communities in Indonesia that use L. coromandelica in their daily lives. A literature review for this paper was conducted in October 2023 using scientific articles available online, including papers from various journal websites, undergraduate theses in college repositories, accessible e-books, and conference proceedings related to Lannea coromandelica through google scholar. The results indicate that L. coromandelica is widely utilized throughout Indonesia, including Sumatera, Java, Kalimantan, West and East Nusa Tenggara, Sulawesi, and North Maluku. Most of the usage of L. coromandelica is for medicinal purposes, treating various diseases such as cough, stomach ulcers, sore eyes, fever, diabetes, and post-partum care. Almost all parts of the plant are useful, including the bark, leaves, trunk, twigs, and the entire plant. Thus, bark is the most utilized plant part. However, besides its medicinal uses, L. coromandelica has numerous other utilizations, including firewood, natural fences, natural dyes, cosmetics, and materials for building and boat hulls. The conservation aspect of L. coromandelica must be considered since in several utilization trunk is used for medicinal purposes.